Derivational and Inflectional Morphemes in Native American Winter Stories on Loe.Org Website - Angelina Kusuma Jelita Mawarni; Barli Bram (Hasanuddin University, 2024)
This research identifies most of the types of derivational and inflectional morphemes. It categorizes the process of derivational and inflectional morphemes in the Native American winter stories on the website that is loe.org. The data consists of 22 derivational morphemes and 57 inflectional morphemes. The method was conducted descriptive qualitative. Results showed that adjective to adverb. Most derivational types occur nine times or 40.90 per cent, followed by the suffix –ly. Meanwhile, the most inflectional type is past tense, which used the suffix –ed occurrences 20 times or 35.08 per cent. The results showed six categories of derivational processes, namely the verb to adjective (23.72%), noun to adjective and noun to adverb (13.63%), adjective to adverb (40.90%), verb to verb and adjective to adjective (4.54%). On the other hand, the six categories of inflectional processes are plural (12.05%), past tense (35.08%), progressive (28.07%), past participle (1.75%), superlative (3.50%), and comparative (10.52%).